Attitudes in the Social Context The Impact of Social Network Composition on Individual-Level Attitude Strength. (article). - Visser, Penny S.
Four studies, using both experimental and correlational designs, explore the implications of being embedded within attitudinally congruent versus attitudinally heterogeneous social networks for individual-level attitude strength. Individual embedded within congruent social networks (i. e., made up of others with similar views) were more resistant to attitude change than were individuals embedded within heterogeneous social networks (i. e.,made up of others with a range of views). Mediational evidence suggests that attitudinally congruous social networks may increase attitude strength by decreasing attitudinal ambivalence and perhaps by increasing the certainty with which people hold their attitudes. The results suggest that features of the social context in which an attitude in held have important implications for individual-level attitude strength. -- (from the author).
Keywords: Psychology-Periodicals.